The Influence of Competence, Organizational Commitment on Village Government Performance Through Village Financial Management: Literature Study - Suparwan, Suparwan; Ratnawati, Tri (International Conference On Economics Business Management And Accounting (ICOEMA), 2022)
The purpose of this study was to determine the effect of competence on village financial management, competence on village government performance, organizational commitment to village financial management, organizational commitment to village government performance, village financial management on village government performance, competence on village government performance through village financial management and organizational commitment to performance through village financial management. The literature study were based on empirical studies from any national and international journals. Data collected by using a search engine methods. The results of the study state that competence and organizational commitment have a significant effect on the performance of the village government directly or through village financial management.